Contract Farming and Out Grower Schemes in Less Developed Countries: Definitions, Typologies and Economic Theories - Senanayake, S. M. P. (My University, 2012)
Very little attempt has so far been made to consider the basic economic theories relevant to contract farming and out grower schemes that could provide an insight into the controversies surrounding such programmes. This paper aims at reviewing a few neo classical micro economic theories relevant to contract farming while the views of various schools of thought are also being briefly discussed. These theories might be helpful in analysing the impact of these schemes on farmers, contracting firms and host governments.